See for me [videorecording (DVD)] - Yorke, Adam; Gushue, Tommy; Vos, Lodewijk; Murray, Joseph (Composer); Davenport, Skyler; Coates, Kim, 1958-; Kennedy, Jessica Parker; Vandervoort, Laura (IFC Films, 2022)
A group of thieves break into the luxurious, secluded mansion Sophie is house-sitting. Sophie, a visually impaired former skier, must rely on Kelly, an army veteran living across the country, to help her fight back.